Efficacy of Beauveria bassiana as a Biological Control Agent Against the Brown Planthopper Nilaparvata lugens in Rice Cultivation - Sepe, Muslimin; Rosa, Helda Orbani; Suhardi, Suhardi (Jurnal Biologi Tropis, 2025)
The brown planthopper (Nilaparvata lugens) is a major pest in rice cultivation. Its population can be effectively managed through biological control using the entomopathogenic fungus Beauveria bassiana. This study aimed to evaluate the effectiveness of the entomopathogenic fungus B. bassiana in controlling N. lugens under greenhouse conditions. Applications of B. bassiana at various concentrations revealed that 10⁸ conidia/mL treatment was the most effective, achieving up to 90% mortality within 7 days post-application. This treatment also recorded the lowest LT₅₀ value of 6.736 days and the highest regression value of 0.52, indicating a rapid and effective reduction in pest population. The mortality rate exhibited an increasing trend up to day five, followed by a decline as target population diminished, with cumulative mortality reaching 90% by day seven. These findings demonstrate that a concentration of 10⁸ conidia/mL is the most optimal for biological control of N. lugens using B. bassiana, both in terms of mortality rate and speed of action. The results support the potential of B. bassiana as a promising biological control agent in sustainable pest management strategies for agricultural systems.